Analisis pengaruh daya tarik, atribut islam, dan aksesibilitas terhadap kepuasan wisatawan pada objek pariwisata religi di Menara Kudus - Tasya Alifia Rizqi; M. Aulia Rachman (Nur Science Institute, 2025)
Religious tourism, which often intersects with cultural tourism, has become an attractive phenomenon for many travelers. A prominent destination in this category is Menara Kudus, a site deeply rooted in the history of the Walisongo's spread of Islam. This study aims to measure tourist satisfaction to contribute to the development of exceptional religious tourism. Employing a quantitative approach, data was collected via a questionnaire from 100 Muslim respondents who had visited Menara Kudus. The data was analyzed using Structural Equation Modeling (SEM) with SmartPLS 3. The research offers insights into the cultural, psychological, and economic drivers influencing the travel behavior of Muslim tourists. The findings indicate that tourist attraction, Islamic attributes, and accessibility have a significant positive effect on tourist satisfaction. Therefore, for tourism industry practitioners seeking to attract Muslim visitors to religious sites or other destinations with an Islamic concept, it is crucial to prioritize indicators of the halal concept in terms of accessibility, facilities, and the activities of local small and medium-sized enterprises (SMEs).